Rājayōgaṃ : Nyūyōrkk nagaratiil veccȧ Vivēkānandasvāmikaḷ ceyta pṟasaṅgaṅṅaḷ - Vivekananda, Swami, 1863-1902 (SAMP early 20th-century Indian books project, 1914)
Author's speeches at New York City; translated from English.